Realization of the kilogram using the KRISS Kibble balance. (7th September 2020) - Kim, Dongmin; Kim, MyeongHyeon; Seo, Minky; Woo, Byung-Chill; Lee, Sungjun; Kim, Jong-Ahn; Chae, Dong-Hun; Kim, Mun-Seog; Choi, In-Mook; Lee, Kwang-Cheol
Abstract: In the revised international system of units (SI), the kilogram is realized through methods linking mass to the Planck constant such as the Kibble balance experiment and x-ray crystal density method. We report on the first experiment for kilogram realization at the Korea Research Institute of Standards and Science (KRISS). The masses of two artefacts (platinum–iridium and stainless steel) were measured using the KRISS Kibble balance between December 2019 and January 2020 at a pressure between 3 × 10 –3 Pa and 4 × 10 –3 Pa. The relative standard uncertainty of the realization experiment was 1.2 × 10 –7 . The mass of the platinum–iridium artefact (No. 111) determined by the KRISS Kibble balance experiment was 2 µg different from the mass determined by historical traceability to the international prototype of the kilogram (IPK) in the previous SI. For the stainless steel artefact, the difference in mass value determined by the KRISS Kibble balance and historical traceability was 56 µg.